Analisis Pengetahuan Kewirausahaan Dan Penggunaan Sosial Media Terhadap Keberhasilan Umkm Bidang Kuliner Di Kecamatan Medan Barat - Sally Irawan; Elaine Faustine; Jeselyn Wiminata; Agnes Vanessa (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the influence of entrepreneurial knowledge and the use of social media on the success of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in West Medan District. In today's digital era, the ability of business actors to understand the concept of entrepreneurship and utilize social media effectively is an important factor in increasing competitiveness and business success. This study uses a quantitative approach with a survey method to a number of culinary MSME actors in the area. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The results of the study indicate that both entrepreneurial knowledge and the use of social media have a positive and significant effect on the success of culinary MSMEs. This finding indicates that increasing entrepreneurial competence and optimal use of social media can support the growth and sustainability of small businesses amidst increasingly competitive competition. This study is expected to be a reference for MSME actors and related parties in formulating digital-based business development strategies.